‘Candidatus Pseudomonas auctus’ sp. nov. JDE115 isolated from nodules on soybean (Glycines max) - Md Sahadat Ali; Fatima Tuz Zohora Mony; Michael Evans; Steven Rideout; David Haak; Paulo Vieira; Jonathan D. Eisenback (PLoS ONE, 2025)
A Gram-negative, facultative anaerobic, rod-shaped, motile with peritrichous flagella, fluorescent bacterium, designated ‘Candidatus Pseudomonas auctus’ sp. nov. JDE115, was isolated from soybean root nodules in Virginia and characterized using a comprehensive integrative methodology. Growth of JDE115 occurred with 0–5.0% (w/v) NaCl (optimum 1%), at pH 6.0–10.0 (optimum pH 7.0), and at 10–40°C (optimum 28°C) in LB broth. Phylogenetic analyses based on the 16S rRNA gene placed the isolate as a member of a novel species within the genus Pseudomonas. Phylogenetic analyses based on whole-genome sequences, 16S rRNA, showed JDE115 having the highest similarity to Pseudomonas glycinae MS586. Average Nucleotide Identity (ANI) analysis also revealed the highest similarity of JDE115 to Pseudomonas glycinae MS586 (94.59%), which is below the 95% threshold for species delineation. Genome-to-genome distance analysis (GGDC, Formula 2) showed a maximum value of 57.10% with the same strain, far below the 70% cutoff. The primary isoprenoid quinone detected in JDE115 was ubiquinone-9 (Q-9) and the DNA G + C content was 60.68 mol%. The whole-cell fatty acid profile was dominated by C16:0, C17:0 cyclo, and the summed features 3 (C16:1ω7c and/or C16:1ω6c) and 8 (C18:1ω7c and/or C18:1ω6c). Additional fatty acids detected included 12:0, 14:0, and 18:0. Based on these phenotypic, chemotaxonomic, and phylogenetic data, strain JDE115 is proposed to represent a new species in the genus Pseudomonas, for which the name ‘Candidatus Pseudomonas auctus’ sp. nov. is proposed.